Combined effects of initial water content and heating parameters on solar pyrolysis of beech wood. (15th April 2017) - Zeng, Kuo; Gauthier, Daniel; Li, Rui; Flamant, Gilles
Abstract: The combined effects of feedstock water content and heating parameters (final temperature and heating rate) on solar pyrolysis product distribution, and on the composition and LHV (lower heating value) of the gas products, were investigated. Beech wood sawdust with 0%, 6%, 11% and 41% initial water content were pyrolyzed in a solar reactor at 900, 1200 and 1600 °C with heating rate ranging from 10 to 150 °C/s. Due to the advantage of solar pyrolysis (high temperatures and heating rates), high water content beech wood can be upgraded into CO- and H2 - rich gas products. Under the used operating conditions, the beech wood drying and pyrolysis proceed simultaneously, which gives rise to a process combining pyrolysis, gasification and reforming. As a result, the combined effects of water content and temperature or heating rate are reinforced, which favors tar steam reforming into more gas product. Highlights: Combined effects of water content and heating parameters on products were determined. Pyrolysis of 41 %w H2 O beech wood at high temperature and heating rate produces 65% gas. H2 /CO ratio is about 1 at 1200 °C and 50 °C/s heating rate with 0% and 41% water content. Low temperatures and heating rates favor the production of liquid (about 50%). Pyrogasification mechanisms are analyzed as a function of operation conditions.